Development of Moodle-based PJBL Integrated Hybrid Learning Model for Informatics Subjects - Fitriani HP, Dinda; Darman; Razilu, Zila (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
The development of information and communication technology (ICT) in education has changed the traditional learning paradigm to be more interactive and effective. One of the emerging innovations is the hybrid learning model, which combines face-to-face learning methods with online learning. The main objective of this research is to develop a hybrid learning model integrated with project-based learning with Moodle in informatics subject. This research is included in the development research (R&D) of ADDIE development model. The Moodle-based PJBL Integrated Hybrid Learning Model for Informatics Subjects at SMP Negeri 1 Sampara that has been made is then validated by validators consisting of media validation and material validation, after being validated, a trial is conducted to students, the trial subject is 22 students of class VIII SMP Negeri 1 Sampara. The results of the research on the development of the Moodle-based PJBL Integrated Hybrid Learning Model for Informatics Subjects were declared very feasible based on the results of media validity with an average of 87.18%. and Material Validation 95.51%, and practical use by students based on the results of student trials 85.26%. Thus the Hybrid Learning Model Integrated PJBL Based on Moodle Informatics Subjects at SMP Negeri 1 Sampara, is very feasible to use in informatics learning, and practical to use.